Assessing the Role of the Cadherin/Catenin Complex at the Schwann Cell–Axon Interface and in the Initiation of Myelination - Lewallen, Kathryn A. (Society for Neuroscience, 2011)
Myelination is dependent on complex reciprocal interactions between the Schwann cell (SC) and axon. Recent evidence suggests that the SC–axon interface represents a membrane specialization essential for myelination; however, the manner in which this polarized-apical domain is generated remains a mystery. The cell adhesion molecule N-cadherin is enriched at the SC–axon interface and colocalizes with the polarity protein Par-3. The asymmetric localization is induced on SC–SC and SC–axon contact. Knockdown of N-cadherin in SCs cocultured with DRG neurons disrupts Par-3 localization and delays the initiation of myelination. However, knockdown or overexpression of neuronal N-cadherin does not influence the distribution of Par-3 or myelination, suggesting that homotypic interactions between SC and axonal N-cadherin are not essential for the events surrounding myelination. To further investigate the role of N-cadherin, mice displaying SC-specific gene ablation of N-cadherin were generated and characterized. Surprisingly, myelination is only slightly delayed, and mice are viable without any detectable myelination defects. β-Catenin, a downstream effector of N-cadherin, colocalizes and coimmunoprecipitates with N-cadherin on the initiation of myelination. To determine whether β-catenin mediates compensation on N-cadherin deletion, SC-specific gene ablation of β-catenin was generated and characterized. Consistent with our hypothesis, myelination is more severely delayed than when manipulating N-cadherin alone, but without any defect to the myelin sheath. Together, our results suggest that N-cadherin interacts with β-catenin in establishing SC polarity and the timely initiation of myelination, but they are nonessential components for the formation and maturation of the myelin sheath.